อัตลักษณ์วิถีวัฒนธรรมชุมชนตะปอน อำเภอขลุง จังหวัดจันทบุรี : การจัดการเพื่อพัฒนารูปแบบการท่องเที่ยวอย่างยั่งยืน - โศรกศรี, นภสร (วารสารวิชาการมหาวิทยาลัยราชภัฏภูเก็ต, 2020)
The purposes of this research are to analyze cultural identities and assess the importance of cultural heritage, to study guidelines for development of cultural tourism model, and to prepare suggestions and guidelines for development of cultural tourism model of Tapon Community, Khlung District, Chanthaburi province to be sustainable. This research is a qualitative research. The methods included field survey, participatory observation, in-depth interview, group discussion, participation in cultural activities with the community and research on related documents. The results revealed that Tapon Community houses were tangible cultural heritage sites, such as the old temples: Tapon Noi Temple, Tapon Yai Temple, which were registered as a historic site by the Fine Arts Department due to its outstanding architecture and valuable physical characteristics with potential learning resource and cultural tourism attraction. The tradition of Phra Bat Cloth Procession and local games, such as "Kwien Phra Bat tug of war", are cultural heritage that has value and importance and is the unique identity of the community as a result of belief and faith. The traditions have long been inherited, and they are social activities that encourage love and unity of the people in the community as well as strengthening the relationship between the community and society around Tapon Community. In addition, the community attracts outsiders, including tourists, who receive information from legends or stories related to beliefs and sacredness of the rituals. According to the research results, the focus is on the determination and guidelines for cultural tourism development based on the concept of quality cultural heritage management to create social value and to increase economic value with the participation of all groups, sexes and ages of people of Tapon Community in the management of plans and various projects which are practical and will result in sustainable cultural tourism in Tapon Community.